Titanium Dioxide Nanoparticles: A Novel Approach for Inhibiting Human Papillomavirus - Al-Musawi, Sharafaldin; Almansorri, Abbas. K.; Al-Shirifi, Hider. M. H.; Ahmed, Bara B; Haider, Adawiya J. (Iraqi Journal of Science, 2024)
Nanotechnology products such as titanium dioxide nanoparticles (TiO2-NPs) can be used for viral infections because of their unique characteristics. The current study aimed to determine the impact of TiO2-NPs on HPV type 1 and 2 infections. The characterization of these NPs was performed using dynamic light scattering (DLS), field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), and X-ray diffraction (XRD). The MTT assay was used to determine the toxic impacts of TiO2-NPs on BHK-21 cells. The efficiency of TiO2-NPs was performed using several parameters, including TCID50 and RT-PCR assays. An indirect immunofluorescence assay (IFA) was performed to estimate the inhibitory impact of TiO2-NPs on viral antigen expression, and Acyclovir was used as a reference medicine. When the human papilloma type 1 and 2 viruses exposed to TiO2-NPs at high doses (100 μg/mL) produced 0.3, 1.1, 2.3, and 3.3 log10 TCID50 decreases in infective virus load when compared with control viruses (P<0.0001), these TiO2-NPs doses were related to 24.9%, 35.1%, 47.2%, 59.5%, and 66.6% inhibition percentages that were determined depending on the viral titer as compared to virus control. It is concluded that TiO2-NPs have strong potential for the treatment of face and labial lesions caused by papillomaviruses 1 and 2 and could be used in topical formulations.